PEMBANGUNAN BERKELANJUTAN BERWAWASAN LINGKUNGAN: STRATEGI PENGELOLAAN SAMPAH MELALUI PENDEKATAN PARTISIPATIF - Sufianti, Ely (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Up to now, the government efforts concerning the waste problem remain unsolved. To deal with, three parties involved, namely, government, society and private sector, should work simultaneously and support each other. What has been done by the local government by means of Environment Office or Local Corporate as the responsibility holder of local environment has not performed optimum results.  On the other hand, the society and private sector as the biggest contributors of concrete waste are potential to be involved in solve this environmental problem. Thus, the waste management will be effective when initiated from its source.